EKSISTENSI UPACARA ULUN ONDOT PADA MASYARAKAT ADAT SUKU BULUSU Studi Desa Pungit Kecamatan Sekatak Kabupaten Bulungan Kalimantan Utara - Syaini Syaini (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2017)
The purpouse of this research is to examine the Existances of Ulun Ondot Burial Ceremonial as a traditions of Bulusu Ethnic. The study focus in Pungit Village, Regency of Bulungan, North Kalimantan. The research approach is quantitative methods were used of random sampling technic. The result of this research was shown the tradition of Ulun Ondot as a haritage culture in Bulusu Ethnic. The composition of many tradition in Bulusu Ethnic, likes a wedding, birth or death ceremony as behalf of many haritage in tresury on this society. The roles of local government is very important for the existances of Ulun Ondot Traditions.